The 'Minibulk' system for advancing winter cereal breeding populations. Issue 3 (10th March 2022) - Olson, Eric; Brown‐Guedira, Gina; Noble, Amanda; Smith, Jared; Forsberg, Lance; Brisco, Elizabeth; Brown, Linda
Abstract: Conventional selected‐bulk breeding is a low cost means of advancing populations but requires years of selection in the field to generate fixed lines. Doubled haploid (DH) methods produce fixed lines quickly but without selection and at high cost. The 'Minibulk' system was developed to combine the speed of DHs with the population size and crossover opportunities of selected‐bulk breeding. Breeding populations of winter wheat ( Triticum aestivum L.) were vernalized and advanced at high density in the greenhouse from the F2 to the F4 generation. F4 populations underwent visual selection in the field, and derived lines were genotyped for variants at photoperiod and vernalization alleles and across the genome using genotyping‐by‐sequencing. The number of crossover events and parental genome contributions were determined for recombinant inbred lines (RILs) within populations and among RILs across populations. During vernalization, seeds in all populations germinated and underwent vegetative growth, forming a dense seed mat that was transplanted directly into greenhouse pots. A 22‐h photoperiod accelerated development, and many populations reached physiological maturity as soon as five weeks after transplanting. Increasing the number of seeds planted from 300 in the F2 to 500 in the F3 increased the number of fertile spikes produced, thereby maintaining a larger population size. The number of crossovers detected differed significantly between populations and chromosomes, while the number of crossovers detected in each population was related to marker density. Adoption of the minibulk system by winter cereal breeding programs can lead to significant cost savings and acceleration of the breeding cycle. Core Ideas: The minibulk system integrates rapid generation advancement with high‐density planting. Lines derived using the minbulk system can follow the same timeline as doubled haploids. Minibulks combine the recombination events and population size of selected‐bulk breeding.